2018
DOI: 10.15516/cje.v20i2.2752
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Basic Psychological Needs and Autonomous Motivation in School Context: A Test of Additive, Synergistic, and Balance Hypotheses/Zadovoljavanje osnovnih psiholoških potreba i autonomna motivacija u kontekstu škole: testiranje aditivne, siner

Abstract: The present study examined the influence of the three basic psychological needs on autonomous motivation in educational settings in the light of additive, synergistic, and balance hypotheses. Participants were 679 high school students (M age = 16.16, 49.3% girls). The findings supported the additive hypothesis: all three needs had unique effects on autonomous motivation. The synergistic hypothesis was only partially supported: one two-way interaction between autonomy and competence had effect on autonomous mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…In this sense, autonomous motivation in the educational context involves engagement in learning (Hafen et al, 2012), drives and directs behavior (Deci & Ryan, 2008), leads to effort (Mouratidis & Michou, 2011), involves self-governance and being the initiator of actions to achieve high grades (Soenens & Vansteenkiste, 2005), and leads to second language proficiency (Joe et al, 2017). Autonomous motivation enables students to achieve the best academic quality through high performance, problem-solving skills, and mastery of conceptual content (Raižienė et al, 2018). Similarly, autonomous motivation plays an important role in English language learning because it automatically influences students' learning engagement (Wang & Liu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, autonomous motivation in the educational context involves engagement in learning (Hafen et al, 2012), drives and directs behavior (Deci & Ryan, 2008), leads to effort (Mouratidis & Michou, 2011), involves self-governance and being the initiator of actions to achieve high grades (Soenens & Vansteenkiste, 2005), and leads to second language proficiency (Joe et al, 2017). Autonomous motivation enables students to achieve the best academic quality through high performance, problem-solving skills, and mastery of conceptual content (Raižienė et al, 2018). Similarly, autonomous motivation plays an important role in English language learning because it automatically influences students' learning engagement (Wang & Liu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Based on Raižienė et al (2018) and Sheldon and Filak (2008), who found that satisfaction of need for autonomy, competence, and relatedness was positively related to autonomous motivation, we anticipated autonomous motivation to be positively predicted by need satisfaction and negatively predicted by need frustration. The opposite pattern of relations was hypothesized for controlled motivation (Hypothesis 1).…”
Section: Introductionmentioning
confidence: 97%
“…In the context of learning English as a foreign language (EFL), it has also been found that need‐supportive classrooms facilitate students’ autonomous motivation (McEown, Noels & Saumure, 2014; Noels, 2005, 2009). Moreover, Raižienė, Gabrialavičiūtė, Garckija, and Silinskas (2018), in an attempt to clarify the relation of each separate psychological need to students’ quality of motivation, showed that satisfaction of each of the three psychological needs has a unique effect on students’ autonomous motivation, while a balanced satisfaction of the three needs explains additional variance in students’ autonomous motivation.…”
Section: Introductionmentioning
confidence: 99%